Effect of Social Media Marketing Variables on Marketing Performance of MSMEs in Indonesia - Arthika Nauli; Sularsih Anggarawati; Willy Abdillah (The Manager Review, 2023)
The purpose of this study is to find out the effect of social media marketing variables on MSME marketing performance in Indonesia. The type of this research is descriptive research with a quantitative approach. The type of data used is primary data obtained through the distribution of questionnaires. The respondents of this research are MSME actors in Indonesia who use social media in product marketing, the total number of respondents is 205 people. Respondents were taken by non probability sampling and were obtained by distributing online questionnaires. The data analysis methods used are descriptive analysis and multiple regression analysis. Based on field research, the results show that: (1) The variable of content in social media marketing activities have a positive and significant influences on the marketing performance of MSMEs in Indonesia. Therefore, if the information presented in social media marketing is getting better, then the marketing performance of MSMEs will increased; (2) The context variable in social media marketing activities has a positive and significant impact on the marketing performance of MSMEs in Indonesia. Therefore, if the information is presented in the right context on social media marketing, then the marketing performance of MSMEs will increased; and (3) The connection variable in social media marketing activities has a positive and significant impact on the marketing performance of MSMEs in Indonesia. Therefore, if the social media used by MSMEs is well connected with other sites, the MSME marketing performance will increased. Keywords: Content, Context, Connection and Marketing Performance